Corrosion-resistant Ce-doped silane film on stainless steel surface and preparation method
Through Ce-doped silane film technology, combined with alkali washing pre-oxidation and cerium nitrate doping, the problem of corrosion of stainless steel during storage and transportation is solved, and the effect of significantly improving corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411451257.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art has shortcomings in improving the corrosion resistance of stainless steels such as 8Cr4Mo4V, especially during storage and transportation, which are prone to corrosion and lead to economic losses.
Adopt CE doped sircanane membrane technology, improves the corrosion resistance of the silicane membrane through alkaline washing pre -oxidation operation and the doping of nitrate, and explores the impact of the hydrolyzed conditions of Silicane Puppets on the membrane performance.
It significantly improves the corrosion resistance of stainless steel surface CE doped silicane membrane, can effectively prevent the corrosion medium from contacting the matrix, extend the life of stainless steel, and reduce economic losses.
Smart Images

Figure CN119350901A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite materials, and in particular to a corrosion-resistant Ce-doped silane film on the surface of stainless steel and a preparation method thereof. Background Art
[0002] With the development of science and technology, various metal materials are increasingly widely used in many fields, but corrosion is inevitable during the use of metal materials. Steel corrosion is a common material corrosion situation. When steel materials are exposed to humid air, water or other media containing oxygen and electrolytes, oxidation reactions will occur, resulting in rust on the steel surface. This rust will continue to spread and eventually destroy the structure and performance of the steel.
[0003] 8Cr4Mo4V and other stainless steels are the most widely used type of bearing steel in my country. In the short-term storage and transportation before they are put into use, they may corrode when in contact with the atmospheric environment. At present, the research on this type of steel is mainly focused on improving its wear resistance, and there is less research on its corrosion and protection. Therefore, there is an urgent need for an effective and feasible method to improve the corrosion resistance of 8Cr4Mo4V and other stainless steels.
[0004] Alloy steel surface protective coating technology is a common anti-corrosion technology, which aims to form a protective layer on the surface of alloy steel, thereby preventing the alloy steel from contacting with corrosive media in the external environment and extending the service life of the alloy steel. Among them, silanization treatment, as a technology with shorter processing time and lower processing cost, has attracted much attention in the field of protective coatings. However, due to the difficulty of silanization treatment in film formation on the surface of materials and the low corrosion resistance of silane films, this technology sometimes cannot meet actual needs, thus affecting its large-scale application. In actual applications, since the thickness and integrity of the pure silane film cannot be fully guaranteed, the protective performance of the silane film alone is limited. At the same time, studies have shown that silane films do not have self-healing properties. As a physical barrier, they can only prevent corrosive compounds from penetrating into metal substrates.
[0005] Therefore, in order to improve the corrosion resistance of steel and reduce the economic losses caused by corrosion during short-term storage and transportation before being put into use, it is urgent to develop a Ce-doped silane film material on the surface of stainless steel and a preparation method. Summary of the invention
[0006] In order to improve the corrosion resistance of steel during storage and transportation and reduce the economic losses caused by corrosion, the present invention provides a corrosion-resistant Ce-doped silane film on the surface of stainless steel and a preparation method. The Ce-doped silane film is solidified on the surface of stainless steel to obtain a corrosion-resistant Ce-doped silane film, and the corrosion resistance of the silane film is further improved by alkaline washing pre-oxidation operation and doping with cerium nitrate; in addition, the influence of the hydrolysis conditions of the silane coupling agent on the corrosion resistance of the silane film is explored to maximize the corrosion resistance of the Ce-doped silane film on the surface of stainless steel.
[0007] In order to achieve the above purpose, the following technical solutions are adopted:
[0008] One of the purposes of the present invention is to provide a method for preparing a corrosion-resistant Ce-doped silane film on a stainless steel surface, comprising:
[0009] (1) Matrix pretreatment: cutting, grinding, alkali washing and pre-oxidation of stainless steel;
[0010] (2) Preparation of Ce-doped silane hydrolyzate: dissolving a silane coupling agent in a solution A consisting of ethanol and deionized water to obtain a mixed solution, adjusting the pH of the mixed solution to obtain a solution B, adding a cerium source to the solution B to obtain a Ce-doped silane coupling agent solution, stirring evenly and then standing to hydrolyze to obtain a Ce-doped silane hydrolyzate;
[0011] (3) The pretreated stainless steel is immersed in a Ce-doped silane hydrolyzate for dip coating, followed by a curing treatment to obtain a Ce-doped silane film on the stainless steel surface.
[0012] It is further defined that the stainless steel in (1) is 8Cr4Mo4V and the cutting size is 15mm×20mm×3mm.
[0013] It is further defined that the contents of the components of 8Cr4Mo4V steel are: carbon content is 0.8-0.85wt%, chromium content is 4-4.25wt%, molybdenum content is 4-4.5wt%, vanadium content is 0.9-1.10wt%, nickel content is not more than 0.2wt%, silicon content is not more than 0.25wt%, manganese content is not more than 0.35wt%, cobalt content is not more than 0.25wt%, tungsten content is not more than 0.25wt%, and the balance is iron and impurity elements.
[0014] It is further defined that the grinding process in (1) is to grind the stainless steel using 400, 800, 1200, and 2000 mesh silicon carbide water-abrasive sandpaper in sequence until there are no obvious scratches on the surface of the stainless steel.
[0015] It is further defined that the alkali washing pre-oxidation process in (1) is to use a 5 wt% NaOH solution to alkali wash the stainless steel at room temperature for 10 minutes.
[0016] It is further defined that in (2), the mass fraction of ethanol in solution A is 95%, and the mass fraction of deionized water is 5%.
[0017] It is further defined that the silane coupling agent in (2) is glycidyloxypropyltrimethoxysilane (KH-560) or 2-(3,4)-epoxycyclohexyl)ethyltrimethoxysilane.
[0018] It is further defined that the mass fraction of the silane coupling agent in the mixed solution in (2) is 1 to 3%.
[0019] It is further defined that the pH adjustment process in (2) is to adjust the pH of the mixed solution to 4-6 using glacial acetic acid.
[0020] It is further defined that the cerium source in (2) is a cerium nitrate solution.
[0021] It is further defined that the concentration of the cerium nitrate solution in (2) is 0.01 to 0.0001 mol / L.
[0022] It is further defined that the stirring time in (2) is 1 h.
[0023] It is further defined that the static hydrolysis temperature in (2) is 20 to 40°C and the hydrolysis time is 6 to 24 hours.
[0024] It is further defined that the dipping time in (3) is 5 to 10 minutes and the number of dipping times is 1 to 5 times.
[0025] It is further defined that the curing treatment temperature in (3) is 150-200° C. and the curing treatment time is 10-20 min.
[0026] The second object of the present invention is to provide a corrosion-resistant Ce-doped silane film on the surface of stainless steel prepared according to the above method.
[0027] Beneficial effects achieved by the present invention:
[0028] The present invention successfully prepares a Ce-doped silane film on the surface of stainless steel. Compared with the prior art, the Ce-doped silane film prepared by the present invention can better prevent stainless steel from being corroded. In addition, the Ce-doped silane film on the surface of stainless steel of the present invention also has the following advantages:
[0029] (1) The present invention performs an alkali washing and pre-oxidation operation on the surface of stainless steel to promote the formation of iron oxyhydroxide (FeOOH) on the surface of the steel. The silane film prepared on the pre-oxidation substrate exhibits stronger protective performance, can improve the thickness and uniformity of the silane film, and enhance the silanization effect. After the alkali washing and pre-oxidation treatment, the Ce-doped silane film on the surface of the stainless steel is more compact, thereby enhancing the corrosion resistance of the Ce-doped silane film.
[0030] (2) The Ce-doped silane film prepared by the present invention has a certain protective effect on stainless steel. The silane coupling agent used contains epoxy groups, which will undergo a ring-opening reaction during the curing process, making the silane film more compact and complete. After being doped with cerium nitrate, the corrosion resistance of the silane film is significantly improved. This is because Ce can promote the ring-opening reaction of the epoxy groups during the curing process and increase the compactness of the silane film. At the same time, Ce in the silane film 3+ 、Ce 4+ When corrosion occurs, insoluble substances will be formed and deposited in the area where corrosion occurs, preventing further expansion of corrosion.
[0031] (3) In the electrochemical impedance spectroscopy experiment, immersion experiment, neutral salt spray experiment, and atmospheric hanging experiment, it was found that the Ce-doped silane film prepared by the present invention can effectively prevent the corrosive medium from contacting the substrate. The Ce-doped silane film did not corrode in the immersion experiment; after the salt spray test was carried out for 12 hours, the Ce-doped silane film still had a good protective effect, and the corrosion occurring at the defects of the silane film did not significantly expand, and there were fewer corrosion points, indicating that its corrosion resistance was improved; in the atmospheric hanging experiment, no obvious corrosion occurred on the surface of the Ce-doped silane film; in the electrochemical impedance spectroscopy experiment, the impedance arc radius of the Ce-doped silane film sample was larger, and the impedance modulus was also higher, with the highest impedance value of 245000Ω·cm 2 The phase angle in the low-frequency region is larger, indicating that the Ce-doped silane film has the best density, indicating that the Ce-doped silane film can effectively prevent the contact between the corrosive medium and the substrate; in addition, the hydrolysis conditions of the silane coupling agent were investigated to obtain the optimal experimental conditions for Ce-doped silane film on the stainless steel surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The results of the immersion experiments of the Ce-doped KH-560 silane film on the surface of 8Cr4Mo4V steel prepared in Example 1 and the KH-560 silane film prepared in Comparative Example 1 in different simulated environments;
[0033] Figure 2 The experimental results of the Ce-doped KH-560 silane film on the surface of 8Cr4Mo4V steel prepared in Example 1 and the KH-560 silane film prepared in Comparative Example 1 in a neutral salt spray environment, wherein (a), (f) 0h, (b), (g) 3h, (c), (h) 6h, (d), (i) 9h, (e), (j) 12h;
[0034] Figure 3 The macroscopic morphology of the Ce-doped KH-560 silane film on the surface of 8Cr4Mo4V steel prepared in Example 1 in the atmospheric hanging test, where (f) 30d, (g) 60d, (h) 90d, (i) 120d, (j) 150d;
[0035] Figure 4 Electrochemical impedance spectra (Nyquist diagrams) of Ce-doped silane films prepared using cerium nitrate solutions of different concentrations in Example 1, Example 10, and Example 11;
[0036] Figure 5 Electrochemical impedance spectra (Bode modulus diagram) of Ce-doped silane films prepared using cerium nitrate solutions of different concentrations in Example 1, Example 10, and Example 11;
[0037] Figure 6 Electrochemical impedance spectra (Bode phase angle diagram) of Ce-doped silane films prepared using cerium nitrate solutions of different concentrations in Example 1, Example 10, and Example 11;
[0038] Figure 7 Electrochemical impedance spectra (equivalent circuit diagram) of Ce-doped silane films prepared using cerium nitrate solutions of different concentrations in Example 1, Example 10, and Example 11;
[0039] Figure 8 This is a graph showing the results of an immersion test of the 8Cr4Mo4V steel substrate of Comparative Example 2 in different simulated environments;
[0040] Fig. 9 The experimental results of the 8Cr4Mo4V steel substrate of Comparative Example 2 in a neutral salt spray environment are shown in Figure 2, where (a) 0h, (b) 0.5h, (c) 1h, (d) 1.5h, and (e) 2h;
[0041] Fig.10 These are the macroscopic morphologies of the atmospheric hanging test of the 8Cr4Mo4V steel substrate of Comparative Example 2, where (a) is 30d, (b) is 60d, (c) is 90d, (d) is 120d, and (e) is 150d. DETAILED DESCRIPTION
[0042] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments are only used to better understand the technical solutions of the present invention and should not be understood as limiting the protection scope of the present invention. For technicians in the field to which the present invention belongs, other different forms of changes or modifications can be made on this basis. It is not necessary and impossible to enumerate all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
[0043] Unless otherwise specified, the materials, reagents, methods and instruments used in the following examples are conventional materials, reagents, methods and instruments in the art and can be obtained through commercial channels by those skilled in the art.
[0044] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.
[0045] The 8Cr4Mo4V steel used in this experiment was provided by China Aero Engine Harbin Bearing Co., Ltd.
[0046] Example 1
[0047] (1) 8Cr4Mo4V stainless steel is used, and the components are as follows: carbon content is 0.8-0.85wt%, chromium content is 4-4.25wt%, molybdenum content is 4-4.5wt%, vanadium content is 0.9-1.10wt%, nickel content is not more than 0.2wt%, silicon content is not more than 0.25wt%, manganese content is not more than 0.35wt%, cobalt content is not more than 0.25wt%, tungsten content is not more than 0.25wt%, and the balance is iron and impurity elements;
[0048] The stainless steel was cut into samples with a size of 15 mm × 20 mm × 3 mm using a wire cutting machine, and then the 8Cr4Mo4V steel substrate was polished using 400, 800, 1200, and 2000 mesh silicon carbide water-abrasive paper in sequence to make the surface free of obvious scratches. The polished steel substrate was first rinsed with deionized water, and then ultrasonically treated with anhydrous ethanol for 10 min. After ultrasonic treatment, it was washed and dried with deionized water, and then placed in 500 mL of 5wt% NaOH solution for alkali washing and pre-oxidation to remove oil and hydroxylation. The alkali washing temperature was room temperature and the time was 10 min. After alkali washing, the 8Cr4Mo4V steel substrate was rinsed with deionized water and dried for standby use.
[0049] (2) Solution A (500 mL) was prepared using anhydrous ethanol and deionized water, wherein the mass fraction of ethanol in solution A was 95% and the mass fraction of deionized water was 5%, KH-560 was dissolved in solution A to obtain a mixed solution, wherein the mass fraction of KH-560 in the mixed solution was 2%, and the mixed solution was adjusted to pH 4 using glacial acetic acid to obtain solution B, 0.001 mol / L cerium nitrate solution was added to solution B to obtain a Ce-doped KH-560 solution, and the solution was stirred on a magnetic stirrer for 1 h, and then placed in a 40° C. constant temperature water bath for hydrolysis for 24 h to obtain a Ce-doped KH-560 silane hydrolyzate;
[0050] (3) The steel substrate was immersed in Ce-doped KH-560 silane hydrolyzate for 5 min and then taken out and blown dry. The dipping was repeated twice and then placed in a drying oven at 180°C for curing for 15 min to obtain a Ce-doped KH-560 silane film on the surface of 8Cr4Mo4V steel.
[0051] Example 2
[0052] The differences between this embodiment and embodiment 1 are as follows: the hydrolysis temperature in (2) is 20° C., the mass fraction of KH-560 in the mixed solution is 1%, and the hydrolysis time is 6 h. The remaining operation process and parameter settings are the same as those in embodiment 1.
[0053] Example 3
[0054] The differences between this embodiment and embodiment 1 are as follows: the hydrolysis temperature in (2) is 30° C., the mass fraction of KH-560 in the mixed solution is 3%, and the hydrolysis time is 12 h. The remaining operation process and parameter settings are the same as those in embodiment 1.
[0055] Example 4
[0056] The differences between this embodiment and embodiment 1 are as follows: the hydrolysis temperature in (2) is 20° C., the pH of solution B is 5, the mass fraction of KH-560 in the mixed solution is 3%, and the remaining operation process and parameter settings are the same as those in embodiment 1.
[0057] Example 5
[0058] The difference between this embodiment and embodiment 1 is that the hydrolysis temperature in (2) is 30° C., the pH of solution B is 5, and the hydrolysis time is 6 h. The rest of the operation process and parameter settings are the same as those in embodiment 1.
[0059] Example 6
[0060] The differences between this embodiment and embodiment 1 are as follows: the pH of solution B in (2) is 5, the mass fraction of KH-560 in the mixed solution is 1%, and the hydrolysis time is 12 h. The remaining operation process and parameter settings are the same as those in embodiment 1.
[0061] Example 7
[0062] The differences between this embodiment and embodiment 1 are as follows: the hydrolysis temperature in (2) is 20° C., the pH of solution B is 6, and the hydrolysis time is 12 h. The remaining operation process and parameter settings are the same as those in embodiment 1.
[0063] Example 8
[0064] The differences between this embodiment and embodiment 1 are as follows: the hydrolysis temperature in (2) is 30° C., the pH of solution B is 6, the mass fraction of KH-560 in the mixed solution is 1%, and the remaining operation process and parameter settings are the same as those in embodiment 1.
[0065] Example 9
[0066] The differences between this embodiment and embodiment 1 are as follows: the pH of solution B in (2) is 6, the mass fraction of KH-560 in the mixed solution is 3%, and the hydrolysis time is 6 h. The remaining operation process and parameter settings are the same as those in embodiment 1.
[0067] Example 10
[0068] The difference between this embodiment and embodiment 1 is that the concentration of the cerium nitrate solution in (2) is 0.0001 mol / L, and the rest of the operation process and parameter settings are the same as those in embodiment 1.
[0069] Embodiment 11
[0070] The difference between this embodiment and embodiment 1 is that the concentration of the cerium nitrate solution in (2) is 0.01 mol / L, and the rest of the operation process and parameter settings are the same as those in embodiment 1.
[0071] Comparative Example 1
[0072] The difference between this comparative example and Example 1 is that no cerium nitrate solution is added in (2), and the rest of the operation process and parameter settings are the same as those in Example 1.
[0073] Comparative Example 2
[0074] The difference between this comparative example and Example 1 is that no silane film is prepared, and only 8Cr4Mo4V steel substrate is used for testing.
[0075] Performance Testing
[0076] (1) Immersion test
[0077] The corrosion resistance of the Ce-doped KH-560 silane film prepared in Example 1, the single KH-560 silane film prepared in Comparative Example 1, and the 8Cr4Mo4V steel substrate of Comparative Example 2 was tested by immersion experiments in different simulated environments (immersion in marine atmosphere simulated liquid; immersion in industrial atmosphere simulated liquid; immersion in urban atmosphere simulated liquid; immersion in marine industrial atmosphere simulated liquid). The results are as follows: Figure 1 , Figure 8As shown, it can be seen that compared with the 8Cr4Mo4V steel substrate, the single KH-560 silane film and the Ce-doped KH-560 silane film can both provide better corrosion protection for the steel substrate, but only the KH-560 silane film sample showed very slight corrosion after being immersed in the marine atmosphere simulated liquid and the marine industrial atmosphere simulated liquid. The cerium-doped silane film sample did not show any corrosion in the four simulated liquids, indicating that it has better corrosion resistance and can form a dense and well-integrity protective layer on the surface of the steel substrate. This is because Ce can promote the cross-linking reaction of the silane film and reduce the defects of the silane film on the one hand, and on the other hand, it can also form insoluble substances at the defects to isolate the corrosive medium, thereby reducing the possibility of corrosion.
[0078] (2) Neutral salt spray test
[0079] The corrosion resistance of the Ce-doped KH-560 silane film prepared in Example 1, the single KH-560 silane film prepared in Comparative Example 1, and the 8Cr4Mo4V steel substrate of Comparative Example 2 was tested in a salt spray chamber. The results are as follows: Figure 2 , Fig. 9 As shown. Fig. 9 It can be seen that the 8Cr4Mo4V steel substrate has been severely corroded. As the salt spray time increases, large patches of reddish-brown rust appear on the substrate surface. The original pitting areas are connected as the salt spray settles. The substrate surface is covered with rust and suffers severe corrosion damage. Figure 2 It can be seen that after the single silane film and Ce-doped KH-560 silane film were prepared on the surface of 8Cr4Mo4V steel substrate, the film layer had a good protective effect on the steel substrate. However, with the extension of the experimental time, the surface of the single KH-560 silane film was severely corroded and basically lost its protective effect. The Ce-doped KH-560 silane film sample still had a good protective effect. The corrosion occurring at the defects of the silane film did not expand significantly, and there were fewer corrosion points, indicating that doping Ce can improve the density and integrity of the silane film, further increasing its corrosion resistance.
[0080] (3) Atmospheric hanging test
[0081] The corrosion resistance of the Ce-doped KH-560 silane film prepared in Example 1 and the 8Cr4Mo4V steel substrate of Comparative Example 2 was tested by exposing the samples to the natural atmosphere for a certain period of time. Figure 3 , Fig.10 As shown. Fig.10 It can be seen that the surface corrosion of 8Cr4Mo4V steel substrate gradually worsens with the increase of storage time, and the corrosion resistance is poor. Figure 3It can be seen that compared with the corrosion of 8Cr4Mo4V steel substrate, Ce-doped KH-560 silane film has a better protective effect on the substrate and no obvious corrosion phenomenon occurs.
[0082] (4) Copper sulfate drip test
[0083] The Ce-doped KH-560 hydrolyzate obtained in Example 1-9 was subjected to a copper sulfate drop test. This experiment is usually used as an accelerated experiment to study corrosion resistance. Through the copper sulfate titration test, the corrosion resistance of the metal surface protective film to the metal substrate can be quickly and intuitively tested. Copper sulfate titration test method: According to the preparation method of the phosphating film test solution in the standard GB / T 3824-1999, copper sulfate, sodium chloride, and hydrochloric acid solution are mixed into a test solution according to the standard content, and the prepared copper sulfate titration test solution is dropped onto the surface of the test substrate. The test solution will gradually penetrate the film layer and react with the metal substrate to produce the following chemical reaction:
[0085] 2Fe+3Cu 2+ →3Cu+2Fe 3+
[0086] Start timing from the time when the copper sulfate test liquid drops onto the surface of the sample, and stop timing when 1 / 3 of the area is occupied by red rust. The copper sulfate titration resistance time of the sample is obtained. The results are shown in Table 1.
[0087] Table 1 Color change time of the copper sulfate drop test of Ce-doped KH-560 hydrolyzate obtained in Example 19
[0088]
[0089]
[0090] It can be seen from the experimental data in Table 1 that when the hydrolysis temperature is 40°C, the pH of solution B is 4, the mass fraction of silane is 2%, and the hydrolysis time is 24h, the discoloration time of the silane hydrolyzate is longer, indicating that the Ce-doped silane film has the strongest corrosion resistance. This is because KH-560 is neutral when dissolved in ethanol-water solution, and its spontaneous hydrolysis rate is slow. The addition of glacial acetic acid can promote its hydrolysis reaction. However, when the pH is too low, the acidity is too strong and will damage the matrix, resulting in a decrease in corrosion resistance. Therefore, the pH of the hydrolyzate is adjusted to 4 using glacial acetic acid. Since the ethanol in the hydrolyzed solution at 40°C evaporates, the hydrolysis time is preferably 24h considering the film-forming effect and stability of the hydrolyzate.
[0091] (5) Electrochemical impedance spectroscopy
[0092] Electrochemical impedance tests were performed on the Ce-doped KH-560 silane films obtained in Example 1, Example 10, and Example 11. Electrochemical impedance spectroscopy determination method: The electrochemical test was performed using an Autolab electrochemical workstation. The test solution was an atmospheric simulation solution of different environments. A three-electrode system was used. The working electrode was 8Cr4Mo4V steel with a size of 15 mm × 20 mm × 3 mm. The reference electrode was a saturated calomel electrode. The auxiliary electrode was a platinum wire electrode. By changing the frequency of the sine wave, a series of impedances, impedance moduli, and phase angles at different frequencies can be obtained. The test parameters were a frequency of 0.00001 to 0.1 Hz, an AC amplitude of 10 mV, and a selection of Figure 7 The equivalent circuit of is fitted and analyzed, where Rs is the solution resistance, Q1 is the silane film capacitance, R1 is the silane film resistance, Q2 is the double layer capacitance, R2 is the double layer charge transfer resistance, and n is the index in the constant phase angle element. The test results are shown in Figure 4 , Figure 5 , Figure 6 , Figure 7 With Table 2.
[0093] Table 2 Electrochemical impedance spectroscopy fitting parameters of Ce-doped KH-560 silane films prepared in Examples 1, 10 and 11
[0094]
[0095] From the data in Table 2, it can be seen that when the concentration of cerium nitrate solution is 0.001 mol / L, the impedance arc radius and impedance modulus of the prepared Ce-doped silane film are the largest, and the corresponding impedance value is 245000Ω·cm 2 The phase angle in the low-frequency region is the largest, and the density of the silane film is the best, which can effectively prevent the corrosive medium from contacting the substrate. Continuing to increase the concentration of the cerium nitrate solution will reduce the cross-linking degree of the silane film during the film formation process of the silane film, thereby affecting the integrity of the silane film, which is not conducive to the corrosion resistance of the silane film.
[0096] The Ce-doped silane film on the stainless steel surface prepared by the technical solution of the present invention has good corrosion resistance. The film layer did not corrode in the immersion experiment, and still had a good protective effect after the salt spray test was carried out for 12 hours. The corrosion occurred at the defects of the silane film did not expand significantly, and there were fewer corrosion points, indicating that the corrosion resistance was improved. The Ce-doped silane film did not have obvious corrosion on the surface in the atmospheric hanging test. The impedance arc radius of the Ce-doped silane film sample was larger, the impedance modulus was also higher, and the phase angle in the low-frequency region was larger, indicating that the Ce-doped silane film had the best density and could effectively prevent the corrosive medium from contacting the substrate.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a corrosion-resistant Ce-doped silane film on a stainless steel surface, characterized in that: include: (1) Matrix pretreatment: cutting, grinding, alkali washing and pre-oxidation of stainless steel; (2) Preparation of Ce-doped silane hydrolyzate: dissolving a silane coupling agent in a solution A consisting of ethanol and deionized water to obtain a mixed solution, adjusting the pH of the mixed solution to obtain a solution B, adding a cerium source to the solution B to obtain a Ce-doped silane coupling agent solution, stirring evenly and then standing to hydrolyze to obtain a Ce-doped silane hydrolyzate; (3) The pretreated stainless steel is immersed in a Ce-doped silane hydrolyzate for dip coating, followed by a curing treatment to obtain a Ce-doped silane film on the stainless steel surface.
2. The preparation method according to claim 1, characterized in that: The stainless steel in (1) is 8Cr4Mo4V, and the cutting size of the stainless steel is 15mm×20mm×3mm.
3. The preparation method according to claim 1, characterized in that: The grinding process in (1) is to grind the stainless steel with 400, 800, 1200 and 2000 mesh silicon carbide water-abrasive sandpaper in sequence until there are no obvious scratches on the surface of the stainless steel.
4. The preparation method according to claim 1, characterized in that: The alkali washing pre-oxidation process in (1) is to use a 5wt% NaOH solution to alkali wash the stainless steel at room temperature for 10 minutes.
5. The preparation method according to claim 1, characterized in that: In the above (2), the mass fraction of ethanol in solution A is 95%, and the mass fraction of deionized water is 5%.
6. The preparation method according to claim 1, characterized in that: The silane coupling agent in (2) is glycidyloxypropyltrimethoxysilane or 2-(3,4)-epoxycyclohexyl)ethyltrimethoxysilane; The mass fraction of the silane coupling agent in the mixed solution is 1-3%.
7. The preparation method according to claim 1, characterized in that: The pH adjustment process in (2) is to use glacial acetic acid to adjust the pH of the mixed solution to 4-6; The cerium source in (2) is a cerium nitrate solution, and the concentration of the cerium nitrate solution is 0.01 to 0.0001 mol / L.
8. The preparation method according to claim 1, characterized in that: The stirring time in (2) is 1 h; The static hydrolysis temperature in (2) is 20 to 40° C., and the hydrolysis time is 6 to 24 hours.
9. The preparation method according to claim 1, characterized in that: The dipping time in (3) is 5 to 10 minutes, and the dipping times are 1 to 5 times; The curing treatment temperature in (2) is 150-200° C., and the curing treatment time is 10-20 minutes.
10. A corrosion-resistant Ce-doped silane film on a stainless steel surface, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of corrosion-resistant zirconium-silicon composite film
CN121110010A
Self-repairing coating and preparation method thereof
CN121575380A